Ethiopia : Decentralization, Delivery and Accountability - World Bank (Washington, DC, 2013)
One of the fruits of this partnership was the preparation of an unusually rich set of background papers, under the umbrella of a process-driven Institutional and Governance Review (IGR); this Analytical and Advisory work was skillfully designed to support the design and implementation of PSCAP. Some of the papers focused on policy; others provided qualitative assessments of the realities on the ground; yet others benchmarked different facets of the governance environment, as a basis for monitoring going forward. A comprehensive synthesis of these IGR papers (referenced in Part A of the bibliography) is neither necessary not desirable; they stand on their own terms. (Also: see the powerpoint overview in Appendix 1 of Ethiopia's decentralization experience prepared by the World Bank team which led the process.). The objectives of this IGR summary are more modest, namely to; Provide (following staff turnover in the World Bank team) an entry point of access to some of the rich materials which have been prepared under the IGR umbrella; draw on the materials (plus other background material on Ethiopia) to provide a qualitative, on-the-ground sense of the extent to which the 2002 reforms have transformed the local governance realities; highlight some of the important base-line benchmarking exercises which were completed under the IGR umbrella, and which provide a key basis for monitoring progress going forward ; and point to some ways in which benchmarking can support the broader objective of strengthening the accountability for performance of Ethiopia's government, in the context of the political realities prevailing in 2006.